STRUCTURE OF BOXERS´ MORPHOLOGICAL CHARACTERISTICS - Benin Murić; Izet Kahrović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
We wanted to help solving the problems we meet every day, and through this research we did. Research was done on population of boxers 15-19 years old, who compete in Serbian Youth League. We keep being asked: "How big is the morphological characteristics influence on a boxer`s success? While selecting boys for boxing, on which morphological characteristics we need to pay our attention most?" Based on results we got in this research, boys must have a good relation of height and weight, and relatively long legs and arms.